Optimizing health screening education to prevent the double burden of malnutrition in early childhood educational institutions (ECD) - Adi Sucipto; Desty Ervira Puspaningtyas; Yunita Indah Prasetyaningrum; Lala Budi Fitriana; Adams Bagus Pratama; Akhmad Surya Kuncara (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Double nutritional burden is a health problem that often occurs in developing countries, one of which is Indonesia. A double nutritional burden is characterized by the presence of conditions of undernutrition and overnutrition at the same time in an area. The double nutritional burden is a serious problem that can impact children.s growth, development, and long-term health. The incidence of underweight, overweight, and stunting is still found at 6-10% in EDC Allifa.Objectives: To evaluate the impact of health education as a preventive action to overcome the problem of double nutritional burden on young children at Early Childhood Education Institutions (ECD).Methods: The research method used was a quasi-experimental design with the One-Group Pretest-Posttest Design. The research was conducted in July 2023 at EDC of Allifa with all 14 EDC teachers. The intervention is in the form of providing health education to EDC  teachers. A paired T-Test was used to know the effectiveness of the education.Results: The average pretest knowledge score was 78,21 while the posttest average was 92,50. The difference in average score before and after providing education is 14,92 with a p-value of 0,001 (CI 95%).Conclusion: There is a significant difference in knowledge scores between before and after being given health education. This shows that the health education provided has had an impact on participants. knowledge, with an increase in knowledge scores.